Patterns of growth factor usage and febrile neutropenia among older patients with diffuse large B-cell non-Hodgkin lymphoma treated with CHOP or R-CHOP: the Intergroup experience (CALGB 9793; ECOG-SWOG 4494). Issue 8 (3rd August 2017) - Morrison, Vicki A.; Weller, Edie A.; Habermann, Thomas M.; Li, Shuli; Fisher, Richard I.; Cheson, Bruce D.; Peterson, Bruce A.
Abstract: Patterns of myeloid growth factor (GF) usage and febrile neutropenia (FN) were examined in patients >60 years of age with diffuse large B-cell non-Hodgkin lymphoma (DLBCL) enrolled on CALGB 9793/ECOG-SWOG 4494, receiving initial therapy with cyclophosphamide, doxorubicin, vincristine, prednisone (CHOP) or rituximab + CHOP (R-CHOP). Myeloid GFs were administered to 256/520 (49%) patients. Indications for use were: prevent dose reduction/dose delay (81%, 207/256); treat FN or non-febrile neutropenia (NFN) (19%, 48/256). One or more FN episodes occurred in 41% (212/520) of patients, with FN most often in cycle 1 (38% of episodes). In multivariate analysis, risk factors for FN included age >65 years (odds ratio (OR) = 2.6, 95% CI: [1.4, 4.9]) and anemia (hemoglobin <12 g/dl) (OR =2.2, 95% confidence intervals (CI): [1.4, 3.5]. Myeloid GF use was common in this older DLBCL population receiving CHOP-based therapy, as was FN, especially during cycle one. Risk factors predictive for FN should be used prospectively to identify patients for whom myeloid GFs are best utilized.